Outcomes and patterns of failure in solitary plasmacytoma: A multicenter rare cancer network study of 258 patients - (:unkn) unknown (ELSEVIER SCIENCE INC, 2006)
Purpose: To assess the outcomes and patterns of failure in solitary plasmacytoma (SP). Methods and Materials: The data from 258 patients with bone (n = 206) or extramedullary (n = 52) SP without evidence of multiple myeloma (MM) were collected. A histopathologic diagnosis was obtained for all patients. Most (n = 214) of the patients received radiotherapy (RT) alone; 34 received chemotherapy and RT, and 8 surgery alone. The median radiation dose was 40 Gy. The median follow-up was 56 months (range 7-245). Results: The median time to MM development was 21 months (range 2-135), with a 5-year probability of 45%. The 5-year overall survival, disease-free survival, and local control rate was 74%, 50%, and 86%, respectively. On multivariate analyses, the favorable factors were younger age and tumor size < 4 cm for survival; younger age, extramedullary localization, and RT for disease-free survival; and small tumor and RT for local control. Bone localization was the only predictor of MM development. No dose-response relationship was found for doses > 30 Gy, even for larger tumors. Conclusion: Progression to MM remains the main problem. Patients with extramedullary SP had the best outcomes, especially when treated with moderate-dose RT. Chemotherapy and/or novel therapies should be investigated for bone or bulky extramedullary SP. (c) 2006 Elsevier Inc.
Keywords: solitary plasmacytoma; multiple myeloma; radiotherapy; prognostic factors; EXTRAMEDULLARY PLASMACYTOMA; CELL TUMORS; BONE PLASMACYTOMA; RADIATION-THERAPY; TOXICITY CRITERIA; MULTIPLE-MYELOMA; SOFT-TISSUE; RADIOTHERAPY; IMPACT; NECK